Application of Six Sigma in Control of Enzymes Determination - Ćorić, Jozo (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2014)
Examines Six Sigma methodology for quality control in enzyme assays. Discusses statistical process improvements, defect detection, and sigma scaling for assessing laboratory procedure reliability.